O currículo de Licenciatura em Matemática de uma instituição pública da cidade de São Paulo - Costa, Lia Corrêa da (2015)
This thesis aims to investigate the elaboration and structuralization of the Curriculum of a Mathematics degree course from a public institution in the city of São Paulo. This Curriculum is different from others we know, because there are eleven Math Foundations disciplines, which cover the Basic Education content. To achieve this research we sought support in studies with the theme curriculum and public domain official documents of the institution in its website. This investigation s approach is qualitative and descriptive. We resorted to interviews with two professors of the institution, who were part of the elaboration of the curriculum, and analyses of documents such as the Political Pedagogical Project, the Course Plan and the Course of Study. In general, the analyses enable to affirm that the experiences and the participation of the two professors were fundamental to the elaboration and structuralization of the Math Curriculum, as they observed the difficulties of the new High Education students. Through this Curriculum, we observed that it is possible to articulate contents of Mathematics studies in Basic Education with the Higher Education, what makes it significant to the formation of Mathematics teachers. This study attempts to reveal that the attitude of the teachers and the formatting of the Curriculum were positive aspects in the elaboration of the Curriculum of this Mathematics degree course